The body in Asia - Turner, Bryan S.; Zheng, Yangwen (Asia Pacific studies, 2009)
The past few decades have seen growing interest in the study of the body. However, the increasing number of exciting and influential publications has primarily, if not exclusively, focused on the body in Western cultures. The various works produced by Asian scholars remain largely unknown to Western academic debates even though Asia is home to a host of rich body cultures and religions. The peoples of Asia have experienced colonization, decolonization, and now globalization, all of which make the 'body in Asia' a rewarding field of research. This unique volume brings together a number of schol.